Field facilitation in open and distance learning in resource-constrained environments: a case of Mzuzu University, Malawi - Kalima, Robert Chagwamtsoka (Rhodes University, Faculty of Education, Department of Primary and Early Childhood Education)
As part of the drive to enhance students' learning experiences and success for students pursuing the B.Ed Science programme through distance education at Mzuzu University (Mzuni), the Open and Distance Learning (ODL) Steering Committee of Mzuni introduced the field facilitation strategy in 2014 to provide additional academic support to such students off campus. There have been questions, though, regarding the effectiveness of this strategy in terms of enhancement of student learning and success. This study, therefore, sought to examine the current field facilitation strategy in the B.Ed Science programme under the ODL mode of delivery, with a view to proposing improvements that would be made to the field facilitation strategy so that it enables enhanced learning and success in Science and Mathematics at Mzuni. Efforts to improve the current field facilitation strategy have been informed by an empirically based understanding of the shortfalls and strengths of the existing field facilitation strategy for ODL students in the B.Ed Science programme. To enhance students' learning and success for ODL students in resource-constrained contexts such as Mzuni and similar contexts, the study adopted a qualitative case study design guided by tools from the second generation of the Cultural Historical Activity Theory. Qualitative data was obtained in two phases, a contextual profiling phase and a modified Change Laboratory Workshop phase. The modified Change Laboratory Workshops were conducted through the social media application 'WhatsApp' rather than in person as is usually done. Qualitative data in the contextual profiling phase was obtained from three categories of participants, namely, Science and Mathematics lecturers, Science and Mathematics field facilitators, and Science and Mathematics students. The contextual profiling phase included surveys, focus group interviews, individual interviews with lecturers at Mzuni and the field facilitators from the five satellite learning centres of Mzuni, and document analysis. The contextual profiling data acted as the mirror data for the next phase of data generation (Change Laboratory Workshop phase). The findings indicated that the support currently rendered by field facilitators to ODL Science and Mathematics students was inadequate and consisted of a shallow mode of instruction focusing on v traditional ways of teaching and learning. This meant that the field facilitators focused on lecturing as a pedagogical strategy for supporting the learning of Science and Mathematics. This was largely because the support offered to field facilitators by Mzuni was inadequate and did not empower them to generate their own strategies of conducting field facilitation innovatively and creatively, which would in turn empower the students to engage actively and reflectively in their own learning activities. This was due to structural, historical and cultural tensions that existed in the larger system (the university system). The implementation of the field facilitation strategy was challenged by such conflicts in the university structure which manifested themselves in the smaller activity system (the field facilitation activity system) which is the focus of this study. Thematically, such conflicts included students' attributes, institutional policies, institutional pedagogy and the material and digital divide which Mzuni has not harnessed to support field facilitation. The study further established that institutional sensitivity to the conflicts raised above would result in an improved field facilitation strategy as the conflicts at the higher level (university level) have an impact on what happens in the smaller systems, for example the ODL in general and the field facilitation activity system in particular. The improved field facilitation strategy was supposed to recognise ODL students as students in transit from the traditional face-to-face learning context to the novel ODL learning context. As such, the transitional period of study from secondary school to university, particularly to year one, required an intensive field facilitation support strategy, and thus greater institutional support for both field facilitators and students for enhanced learning experiences and success that would eventually result in improved students' retention and throughput. The findings of this study will therefore inform all those involved in ODL, particularly those in resource-constrained contexts, to be conscious when implementing ODL innovations. Serious consideration of the contexts in which the innovations are to be implemented is critical.
Keywords: Distance education -- Malawi; Mathematics teachers -- Training of; Science teachers -- Training of; Tutors and tutoring; Cultural-historical activity theory